Talk of Pedophilia: The Reflexive Management of Desire. Issue 12 (2nd December 2017) - Williams, Lawrence H.
ABSTRACT: Sociologists have increasingly been using theories and models borrowed from cognitive science and psychology to address questions of personal motivation. One influential model is the dual-process model, a cognitive model which holds that individuals think and act either unconsciously and automatically, or consciously and deliberately. Through an analysis of conversations between individuals who are sexually attracted to minors, however, I find that these individuals' sexual desires cannot be reduced to strictly automatic or deliberate means. Due to the taboo nature of this sexual preference in these individuals' locales, their unconscious sexual desires are frequently called into question and made conscious.